Domestic and International College Students: Health Insurance Information Seeking and Use - Mackert, Michael; Koh, Hyeseung E.; Mabry-Flynn, Amanda; Champlin, Sara; Beal, Anna (Journal of International Students, 2018)
This study aimed to explore perceived barriers to using health insurance and identify discriminant factors between health insurance information seekers and non-seekers. A total of 615 domestic and international college students from a large university in the Southwest completed a cross-sectional survey. Findings imply that campus health providers and staff in international student services should be working closely to communicate to students about health insurance because they are both trying to solve the same basic problems.